Online cash desk for individual entrepreneurs - O. V. Nikiforova (Путеводитель предпринимателя, 2020)
The article deals with the concept of an online cash desk, the principle of its operation, the procedure for switching to an online cash register, administrative fines for violations in the field of implementation of a control and cash equipment (CCE).